Exploring projectification in the public sector: the case of the next stage review implementation programme in the department of health - Schuster, Andrew (Cranfield University, 2015)
Objective: Public projects are used to delivery policy objectives. From a financial perspective, the Major Projects Authority (MPA) estimated a whole life investment of £488 billion for 199 major projects in 2014, only a small subset of the total number of public projects. Given the financial exposure, the impact of endemic public project failures could put the economic health of the nation at risk. This thesis studies the challenges facing public projects. It applies an organisational capabilities lens to investigate projectification, when organisations shift away from functional-based organising (FBO) toward project-based organising (PBO). Research Design: This study adopts an interpretivist research paradigm, with a constructionist epistemology and an idealist ontology, and employs an abductive research strategy. Structurally, it follows the Cranfield Executive Doctorate in Business Administration (DBA) methodology, with a linking document that summarises three complementary research projects: a systematic literature review (SLR) followed by two empirical studies that investigate the Department of Health (DoH) during the early phases of the Next Stage Review Implementation Programme (NSRIP). The findings are derived from over 250 academic literature sources, 100 government publications and 41 semi-structured interviews. ...[cont.]
Keywords: Projectification; Project-based; Publicness; Inheritance; Public sector; Civil service; Capability; Routines; Actors; Project management office; Distinctive